Emotional labor in sports coaching: Development of a model - Lee, Y. H.; Chelladurai, P.; Kim, Y.; Mallett, C. (International Journal of Sports Science and Coaching, 2015)
Coaching in sports represents an emotion-laden context. Many incidents evoke disparate emotions among coaches during practices and competitions, especially in communication with their athletes, the members of the opponents, the referees, the media, and other stakeholders. To manage and express these emotions appropriately, coaches need to perform emotional labor. With a view to examining the dynamic nature of sports coaching world, this paper proposes a conceptual model of emotional labor in coaching based on the literature on both emotional labor and sports. We identify three main types of emotional labor (surface acting, deep acting, and genuine expression) and the associated psychological costs (psychological effort, emotional dissonance, and feeling of authenticity), and link them to the key outcomes of job satisfaction and job burnout. Our model also includes individual difference variables of emotional intelligence and positive affectivity as moderators. Directions for future research and its implications are discussed.